2018
DOI: 10.1111/ecc.12804
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of the Australian radiation oncology workforce: A survey of radiation therapists and radiation oncology medical physicists

Abstract: This study aimed to determine and compare Radiation Therapists' (RTs') and Radiation Oncology Medical Physicists' (ROMPs') perspectives about their profession and workplace, satisfaction with career progression opportunities, and leaving the current workplace. RTs and ROMPs who were currently or had previously worked in Australia were invited to complete an online survey. Univariate and multivariate methods were used for analysis. Participants were 342 RTs and 112 ROMPs with estimated response rates of 14% and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 30 publications
2
19
1
Order By: Relevance
“…This present study complements prior work done on the topic of burnout, as the reported rates of frequent or constant burnout are similar . Burnout appears to be a problematic area for peer support.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This present study complements prior work done on the topic of burnout, as the reported rates of frequent or constant burnout are similar . Burnout appears to be a problematic area for peer support.…”
Section: Discussionsupporting
confidence: 78%
“…While the drivers and consequences of burnout within medical physicists are not well characterized, many medical physicists also share these chaotic work environments. It is postulated that these challenging conditions exist within the work life of the medical physicist as well, and in addition to this high workload, may contribute to the 40% burnout rate of medical physicists …”
Section: Introductionmentioning
confidence: 99%
“…Australian RT research recognises the need to improve communication, peer support, morale, MDT integration, conflict resolution, bullying, and career advancement processes . Overcoming these barriers to staff engagement is vital for individual and organisational growth .…”
Section: Radiotherapy Leadership Strategiesmentioning
confidence: 99%
“…Overcoming these barriers to staff engagement is vital for individual and organisational growth . Possible strategies may include initiating a peer‐support group, collaborative decision‐making, counselling provision, staff recognition, debriefing, incentive programs and resilience training . Improvement of working conditions – staffing levels, pay, flexibility, development opportunities and department structure – may also benefit staff cohesion.…”
Section: Radiotherapy Leadership Strategiesmentioning
confidence: 99%
See 1 more Smart Citation